Building Students’ Information System Value Co-Creation With The Technology Acceptance Model: An Extension Of The S-Dl Theory - Andi Setiawan; Riyadi Riyadi; Kurniani Kurniani; Paniya Paniya; Makmun Riyanto (Cita konsultindo, 2023)
Several studies assess the existence of Students' Information Systems and the desire for reuse behavior is still a gap. The presence of technology for some researchers makes its fears for users. Technology becomes something new and binds users with several rules in operating it into another problem in the presence of the Students' Information System. The principle of S-DL and technology is to assess the problem of creating corporate value with the market. The S-DL logic outlines how technological innovation becomes a driver of service innovation by offering customers the value proposition they desperately want. This study selected 145 respondents with the model testing analysis technique with the SEM-AMOS approach. The results of testing all hypotheses significantly encourage companies to engage and utilize technology in higher education. The results of analyzing the data collected show that the S-DL Principle identified Sustainable Use Decision as a learner's decision to continue using TAM and Information Systems